2007
DOI: 10.1044/1058-0360(2007/029)
|View full text |Cite
|
Sign up to set email alerts
|

Speech-Language Pathologists' Assessment Practices for Children With Suspected Speech Sound Disorders: Results of a National Survey

Abstract: Most participants provided assessments that met federal guidelines to qualify children for special education services; however, additional assessment may be needed to create comprehensive treatment plans for their clients. These results provide a unique perspective on the assessment of children suspected of having SSD and should be helpful to SLPs as they examine their own assessment practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
120
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 27 publications
6
120
1
6
Order By: Relevance
“…Studies have found that, although there are similarities in the parameters assessed, therapists differ in their choice of procedure, 63,254 and this seems to be related to clinicians' beliefs and theoretical perspectives. 261 In line with UK findings, the choice appeared to be influenced primarily by financial constraints although factors such as validity and reliability, versatility, efficiency, ease of administration and familiarity are also important.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found that, although there are similarities in the parameters assessed, therapists differ in their choice of procedure, 63,254 and this seems to be related to clinicians' beliefs and theoretical perspectives. 261 In line with UK findings, the choice appeared to be influenced primarily by financial constraints although factors such as validity and reliability, versatility, efficiency, ease of administration and familiarity are also important.…”
Section: Assessmentmentioning
confidence: 99%
“…A number of studies have explored the assessment procedures used by therapists working with children with communication difficulties and what influences the choices they make 253,254 and, in particular, what formal (standardised) or informal (non-standardised) assessments are used and how uniform the practice is across the profession. 253,255,256 Internationally, a high proportion of therapists report using informal, self-designed assessments.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulability test is used by 95% of the North-American speech-language pathologists (7) , who evaluate this ability by using tasks of syllable and word imitation (2,(8)(9)(10)(11) associated with the use of sensory cues (12)(13)(14) . Some authors use a dynamic evaluation of the stimulability by beginning the test with the application of simple stimuli, and, depending on the child's response, the therapist will be able to define the complexity degree of the next sequence to be tested (sound, syllable, word or sentence) (3,15) .…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic assessment also measures the patient's motivation and zone of proximal development, or learning potential (Kapantzoglou, Restrepo, & Thompson, 2012). Skahan, Watson, and Lof (2007) had similar findings in an investigation in which the assessment procedures of English Language Learners (ELL) children suspected of having speech sound disorders were examined through surveying 1000 SLPs. Of 110 who reported having "non-native English speakers" in their caseloads, their findings revealed informal procedures were the most frequently used method (67%), followed by the use of English-only standardized tests (35%).…”
Section: Assessmentmentioning
confidence: 99%